2019
DOI: 10.21203/rs.2.11860/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiac biomarkers for early detection of cardiac involvement in children with Kawasaki disease: a cross-sectional study

Abstract: Background Kawasaki disease (KD), which is the second most prevalent vasculitis disease in children after IgA vasculitis, can cause serious cardiovascular complications. Early detection of cardiac involvement in KD is an essential part in managing and preventing the cardiac sequels. Although some cardiac biomarkers such as cardiac troponin I (cTnI) and N-terminal pro-brain natriuretic peptide (NT-proBNP) have recently been suggested for early diagnosis of cardiac involvement in patients with KD, their applica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Although COVID-19 is demonstrated to be less severe in children compared to adults, the reports of some devastating and fatal complications following COVID-19 in children and adolescents have generated considerable concern and the number of such reports is rapidly increasing [4] . Kawasaki disease (mucocutaneous lymph node syndrome) is characterized as the most common cause of coronary artery aneurysms in children [5] , [6] , [7] . Several studies have reported a Kawasaki-like illness following COVID-19 called MIS-C [8] , [9] , [10] .…”
Section: Case 1: An Infant With Giant Coronary Artery Aneurysm Due To...mentioning
confidence: 99%
“…Although COVID-19 is demonstrated to be less severe in children compared to adults, the reports of some devastating and fatal complications following COVID-19 in children and adolescents have generated considerable concern and the number of such reports is rapidly increasing [4] . Kawasaki disease (mucocutaneous lymph node syndrome) is characterized as the most common cause of coronary artery aneurysms in children [5] , [6] , [7] . Several studies have reported a Kawasaki-like illness following COVID-19 called MIS-C [8] , [9] , [10] .…”
Section: Case 1: An Infant With Giant Coronary Artery Aneurysm Due To...mentioning
confidence: 99%